Debt servicing problems of low-income countries, 1956-1958 - Avramovic, Dragoslav; Gulhati, Ravi; International Bank for Reconstruction and Development; World Bank. (Baltimore : Johns Hopkins Press, 1960)
This study attempts to show that public loans and grants to underdeveloped countries rose by slightly over 50 per cent between 1955 and 1958. During the same period, the respective receipts of Latin American countries more than doubled, with the increase in short and medium-term loans to relieve balance-of-payments difficulties especially pronounced. The external public debts of some 51 countries rose by 27 per cent, while for the Latin American countries the corresponding increase was over 40 per cent. The bulk of the Latin American debt service consists of repayments. This, in turn, reflects the shortening of the debt structure of these countries, and the concomitant acceleration of the repayment schedules. The book also point out that " at the rate at which loans were being repaid at the beginning of the postwar period, it would have taken on the average 28 years to repay the entire Latin American debt, provided no new debt was incurred. The Latin American countries' capacity to service the debt has been adversely affected by a number of factors. The terms of trade-the relation of export and import prices-have turned against the producers of raw materials and foodstuff.
Includes bibliographical footnotes
usc 18/05/2018; 07/08/2018
Loans
Keywords: Loans; Investments, Foreign; Debts, Public; Debts, External; Economic assistance; Developing countries